HUMAN LANGUAGE AS NATURAL CODING: THE NATURAL GENESIS OF HUMAN LANGUAGE: INSIGHTS FROM THE ODAM TILI THEORY - Mahmudjon Kuchkarov; Marufjon Kuchkarov (World Scientific Research Journal, 2025)
The origins of human language have long been a topic of heated debate, with theories ranging from divine intervention to cultural arbitrariness and biological determinism. The Odam Tili (Human Language) theory offers a groundbreaking alternative, proposing that language emerged as a natural, systematic response to the environment. By examining the archetypal figures of the snake, the tree, and human physiology, this theory suggests that linguistic structures were shaped by repetitive patterns of sound and form found in nature. This paper explores the interplay between these elements, arguing that language is a product of natural coding, deeply rooted in environmental and cognitive necessities.